(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Summary: Traumatic brain injury (TBI) is a complex process resulting into structural brain damage and functional deficits as a result of an external mechanical force. This study aimed to investigate the possible ameliorative effect of Raphia hookeri ethanol extract (RHEE) on induced acute traumatic brain injury in rats. The choice of the plant was based on its reported anti-oxidative property. Thirty-six female Wistar rats were divided into six groups of six animals each. I: CONTROL - distilled water orally; II: RHEE - 100 mg/kg RHEE; III: Sharp trauma brain injury (STBI); IV: STBI+RHEE; V: Blunt trauma brain injury (BTBI); VI: BTBI+RHEE. Brain injury was inflicted using modified weight drop technique on experimental day 1 while RHEE was given orally by gavage for 7 days post-injury. Blood was collected serially 24hrs, 72hrs and 7 days post-trauma for full blood count and differentials of the white blood cells. On day nine, rats were euthanized and brain harvested for biochemical and histological analyses. Trauma significantly (p<0.05) reduced the relative brain weight of rats compared with the control. Lymphocyte count increased while neutrophils reduced in all traumatized rats compared with control group. Both BTBI and STBI significantly (p<0.05) elevated MDA and significantly (p<0.05) reduced the level of GSH, the activities of SOD and CAT enzymes compared with control group. Histologically, the extent of haemorrhage into the subarachnoid and brain parenchyma in STBI and BTBI groups was reduced in the BTBI+RHEE and STBI+RHEE groups. Administration of RHEE reduced oxidative damage and ameliorated neuronal damage in sharp and blunt brain injuries.